IMPLEMENTATION OF SYSTEM ANALYSIS IN A LAW ENFORCEMENT ORGANIZATION, AS A NEED FOR AUTOMATION OF PROCESSING A LARGE DATABASE - Yeskov, Serge V.; Zaіets, Oleksandr M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article is to investigate the nature of the use of analytical methods for processing large data sets. Research methods: the use of the system-structural method and the method of generalization allowed us to analyze the general tendencies of the use of analytical methods. The dialectical method of scientific cognition, as well as methods of analysis, synthesis and abstraction, clarified the content and purpose of the problem under study, identified its main features and structure, as well as the relationship with system analysis. Results: the indicated analytical tools considerably increase the efficiency of investigating the investigated crimes, due to the possibility of drawing up charts (diagrams) of criminal ties (including telephone communication schemes with unlimited number of mobile phones and numbers), event matrices, financial flow diagrams, frequency charts of contacts. Discussion: this section covers the use of analytical methods to protect economic rights, freedoms and interests of individuals in the investigation of criminal offenses. The position on the place of information analysis in counteracting crime is substantiated. The general directions of analytical activity of law enforcement bodies are indicated. Graphically, the place of system analysis in the structure of analytics and related branches of knowledge is depicted. The experience of the European Union and the United States regarding the use of criminal analysis capabilities in combating economic crime is presented. The directions of use of elements of criminal analysis (specialized software) during investigation of economic criminal offenses are indicated. Therefore, one can confidently assert that in order to increase the effectiveness of protecting the economic rights, freedoms and interests of individuals during the investigation of criminal offenses, it is considered necessary and expedient to use the whole arsenal of analytical methods. In order to achieve the maximum level of automation of work, qualitative processing and visualization (visibility) of relationships between individuals, events and individuals in the existing large masses of information in the investigation of multi-episode, complex, latent economic crimes committed by organized criminal groups (groups), it is recommended to use standard software criminal analysis, for example, such software systems as IBM I2 Analyst’s Notebook, IBM I2 iBase8, and others.